2004
DOI: 10.1111/j.1467-7652.2004.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of rotavirus VP6 protein in chloroplasts of transplastomic tobacco is limited by protein stability

Abstract: SummaryRotavirus VP6 is a highly immunogenic major capsid protein that may be useful as a subunit vaccine. The expression of a bovine group A rotavirus VP6 cDNA was examined in tobacco chloroplasts following particle bombardment. Constructs containing the VP6 cDNA under the control of plastid rrn or psbA promoters, or the Escherichia coli trc promoter, were inserted, together with the aadA selectable marker gene, between the rbcL and accD genes of the tobacco plastid genome. The 40-kDa VP6 protein accumulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 59 publications
8
116
1
1
Order By: Relevance
“…HA protein accumulation was assessed in both young and mature leaf tissue from the two transgenic lines by immunoblotting, however, HA protein could not be detected in either case (data not shown). Other studies have also reported difficulty in achieving expression of a viral antigenic protein and a viral antigenic peptide in plant plastids (Birch-Machin et al, 2004, Molina et al, 2004. It is likely that the viral HA gene construct will require additional elements that could confer protein stability, such as candidate N-terminal or C-terminal fusions, to bring about protein accumulation in the lettuce plastid.…”
Section: Resultsmentioning
confidence: 99%
“…HA protein accumulation was assessed in both young and mature leaf tissue from the two transgenic lines by immunoblotting, however, HA protein could not be detected in either case (data not shown). Other studies have also reported difficulty in achieving expression of a viral antigenic protein and a viral antigenic peptide in plant plastids (Birch-Machin et al, 2004, Molina et al, 2004. It is likely that the viral HA gene construct will require additional elements that could confer protein stability, such as candidate N-terminal or C-terminal fusions, to bring about protein accumulation in the lettuce plastid.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, relatively low transcript accumulation in chloroplasts was obtained with the clpP promoter and, unexpectedly, with the full-length rrn promoter. However, since northern blot analyses revealed similar amounts of transcript when the rrn, psbA and trc-derived 5 0 regulatory sequences drove the expression of an alternative gene (Birch-Machin et al 2004), promoter performance and final transcript accumulation can vary significantly with the downstream sequence. In potato plants containing the same promoter/5 0 -UTR (psbA), the rrnB terminator gave the best results, confirming results obtained in tobacco, although variability among terminators was less evident than previously found (Tangphatsornruang et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The pZF7lox plastid transformation vectors are derived from plasmids pZSJH1 (Birch-Machin et al 2004) and pRB95 (Ruf et al 2001). The plastoglobulin35 (PGL35)-ORF without the coding sequence for the transit peptide gene was amplified from pCL61-PGL35 with PGL35-F forward primer introducing a NcoI restriction site at the 5 0 -end and with PGL35-R reverse primer introducing the coding sequence for three TEV protease sites as well as NdeI and XbaI restriction sites at the 3 0 end.…”
Section: Cloning Proceduresmentioning
confidence: 99%